Resistive Switching in the Cu/Si/SiO2/CdS/CuO/Cu Structure Fabricated at Room Temperature - Haneafa Yahya Najm (Tikrit Journal of Pure Science)
This work investigates CuO and CdS (material as nanoparticles mixed with a polymer (Cellulose Acetate)) – based ReRAM having stable resistive switching. It also investigates a new composition of a memory which  is constructed with silicon as a pedestal, silicon oxide SiO2 thermally grown on it and active materials that include of (CuO material as nanoparticles mixed with a polymer (Cellulose Acetate) layer) sandwiched between two electrodes using similar material and CdS layer as a semiconductor n-type. ReRAM memory cell is a structure such as a capacitor that is consist of semiconducting transition metal oxides or insulating exhibiting inverses  resistive switching on applying voltage pulses .The mixed material was coated as a thin layer by using Spin-Coating Instrument. this structure can be switched between low- resistance state (LRS) and high resistance state(HRS);therefore, The present structure behaves as unipolar resistive switching. The resistive behavior will be affected by the top electrode area. This effect  occurs more in big top electrode area (TEL=15.896mm2) where, the constituting voltage (Vforming) is inversely  proportionately  with respect to the top electrode area (A) .Also the (HRS) is inversely proportioned with the (A). The complying current (Icc=20mA) is used for protect the device from the damageable. The fabricated composition has many prosperities, such as Vforming = 7.3volt, Vset = 4volt, VReset = 1.7volt, Finally, the resistance ratio (Rratio) is proportioned directly with the(A) and equal Rratio=157.48 so, this ratio is enough to distinguish amongst the low resistance and the high resistance in a circuit design